2021
DOI: 10.1039/d1ta02926f
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions of CO2molecular activation and 4f levels as electron transport bridges in erbium single atom composite photocatalysts therefore enhancing visible-light photoactivities

Abstract: Only when the interfacial charge separation is enhanced and the CO2 activation is improved, can the heterojunction nanocomposite photocatalyst be brought into full play for CO2 reduction reaction (CO2RR). Here,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…The authors have attributed the greatly improved photocatalytic activity of MOF-525-Co to the boosted separation efficiency of electron-hole pairs in porphyrin units after the Co introduction. Since then, many research works of photocatalytic CO 2 reduction into CO or CH 4 fuel gas have been reported over various single-atom photocatalysts along with the production of H 2 , where H 2 O provides the hydrogen resource 59,[74][75][76]114,[155][156][157][158][159][160][161][162][163][164][165][166]. Li et al have created a unique Fe-N 4 O site supported on nitrogen-rich carbon for photocatalytic CO 2 reduction via a facile top-down strategy (Figures 10A-…”
mentioning
confidence: 99%
“…The authors have attributed the greatly improved photocatalytic activity of MOF-525-Co to the boosted separation efficiency of electron-hole pairs in porphyrin units after the Co introduction. Since then, many research works of photocatalytic CO 2 reduction into CO or CH 4 fuel gas have been reported over various single-atom photocatalysts along with the production of H 2 , where H 2 O provides the hydrogen resource 59,[74][75][76]114,[155][156][157][158][159][160][161][162][163][164][165][166]. Li et al have created a unique Fe-N 4 O site supported on nitrogen-rich carbon for photocatalytic CO 2 reduction via a facile top-down strategy (Figures 10A-…”
mentioning
confidence: 99%
“…XPS results further confirmed the existence of N, P, and Er elements ( Figure 4 A). Also, as shown in Figure 4 B, the high-resolution spectrum of Er can be divided into three peaks, which are assigned to Er 2 O 3 (168.3 eV), 19 Er (169.4 eV), 19 and Er 3+ (171.0 eV), 20 indicating that Er is combined with biochar, which may be in the form of an elemental substance (Er) and oxide (Er 2 O 3 ). The abundant electronic structure of Er may be related to its interaction with biochar.…”
Section: Resultsmentioning
confidence: 99%
“…Rare-earth elements are rich in reserves, own a unique electronic structure, possess optical and magnetic properties, and have many applications in scientific research and industry . The upconversion characteristics of rare-earth elements can broaden the light absorption region, and their unique electronic structure is conducive to the rapid transfer of electrons, making their modified inorganic semiconductor photocatalysts show great advantages in solar energy conversion. , However, the current use of rare-earth elements is mainly focused on doping into photocatalysts, and there is little research on the supported rare-earth materials. − In addition, under our knowledge, the research on the photocatalytic hydrogen production of catalysts loaded with rare-earth materials has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…How to greatly improve charge transfer at the heterogeneous interface is still the focus of current research work. [34][35][36] Atomically thin semiconductors can provide a large number of low-coordination surface atoms, which can be used as the catalytic center for CO 2 reduction to improve the photocatalytic activity. The ultra-thin thickness can also shorten the distance of charge transfer, so that the photo-generated carriers can more easily migrate from the inside to the surface.…”
Section: Introductionmentioning
confidence: 99%